HALAL PRODUCTS AND FORMAL PIETY MUSLIM MIDDLE-CLASS LIFE IN THE ANALYSIS OF RELIGIOUS RECEPTION THEORY - Malik, Abdul; Irwan, Muh.; Wathani, Syamsul (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2022)
The Muslim middle class is a religious group that lives in commodified Islam and is self-commodified with Islam for the benefit of life. Their presence represents two entities, the middle class is attached to material and Muslims are attached to religiosity. These two entities emphasize their existence as new religious communities. This article is an exploratory-verificative research from the results of field research on the Muslim middle class, especially in the study of religious behavior (religious performance). This article focuses on analyzing research gaps, data, theory and theorizing of research results into the scientific development of the sociology of religion. The analytical framework used is the analysis of religion as a tradition and doctrinal reception. With this analytical framework, this article finds several conclusions: The Muslim middle class has a strong dependence on halal products. There are two models of halal in products and social cognition of the Muslim middle class, namely: Islamic products and Islamicized products. Halal status is a driving factor that directs the consumption and consumption of halal products for the middle class, providing assurance of religious morals and an Islamic life. The Muslim middle class also expresses popular culture and formal/symbolic piety in public spaces. Formal piety includes: Islamic pants, beards, syar'i hijab, syar'i robes, veils, syar'i fashion, syar'i cosmetics and other economic artifacts. By characterizing the consumption of halal products and formal piety, the religious behavior of the Muslim middle class is in the low tradition plains. Religious traditions themselves are formed from clashes and greetings from the reality or habitus around them. In piety mapping, the Muslim middle class is in the Islamic category in the form of active piety.”